Effectiveness of Arduino Microcontroller-Based Newton's Law Application Experiment to Improve Science Process Skills - Fayolla Octa Riwandi; Naila Fauza; Mitri Irianti (Jurnal Inovasi Pendidikan dan Sains, 2025)
: The problem in this research is that the level of scientific processing skills in particle motion dynamics is still low. An attempt to overcome this problem is to conduct a practical experiment using the Newton's Law Application Experiment Tool based on an Arduino microcontroller. This study used a quasi-experimental type of study with a non-equivalent post-test control group design. The study sample included Grade XI SMA Negeri 3 Pekanbaru students in the 2023/2024 school year with a total of 72 students. Data analysis technique uses descriptive analysis based on students' Scientific Process Skills (SPS) criteria scale. The results of this study show that the application of experimental tools applying Newton's law on the Arduino microcontroller platform has the ability to improve scientific pr The average score of students in the control class was in the low category with a score below 54. Meanwhile, in the experimental class, there were more in the high category (>86). ocessing skills of grade XI SMA Negeri 3 Pekanbaru students learn on particle motion dynamic materials. This study only focused on short-term effects without assessing long-term retention of science process skills